Bartonella henselae Antibodies in Serum and Oral Fluid Specimens from Cats - Alejandra Álvarez-Fernández; Marta Baxarias; David Prandi; Edward B. Breitschwerdt; Laia Solano-Gallego (Pathogens, 2021)
Cats are the primary reservoir host for Bartonella henselae(B. henselae), an etiological agent of human bartonellosis, including cat scratch disease. Although Bartonella DNA has been amplified from salivary swabs from cats, dogs and humans, we are not aware of studies investigating Bartonella antibodies in oral fluid (OF). Using inhouse and commercial immunofluorescence antibody assays (IFA), the objective of this study was to detect and compare antibodies against B. henselae in paired OF and serum specimens from cats. Specimens were collected from shelter and client-owned cats. For serum specimens, B. henselae seroreactivity was 78% for both the inhouse and commercial IFA assays and 56.8% for OF specimens. Comparing serum and OF specimens, there was moderate Kappa agreement (Cohen’s k = 0.434) for detection of B. henselae antibodies. Oral fluid antibodies were more likely measurable in cats with high B. henselae serum antibody titers when compared with low antibody titers. In conclusion, B. henselae OF IFA antibody measurements were less sensitive compared to serum IFA measurements of ≥1:64. Oral fluid antibodies were detected more often in cats with high B. henselae serum antibody titers. Therefore, OF antibodies, detectable by IFA, is of limited utility for epidemiological or diagnostic testing in cats.